Smallpox Vaccination Outcomes and Adverse Event Surveillance of 18 Counties in North Central Florida - Jerne Shapiro; Matthew R. Laidler; Tom Belcuore (University of North Florida, 2006)
Based on the directive from President George W. Bush to prepare the nation better for a possible smallpox attack, Florida enacted Operation Vaccinate Florida- Stage I (OVF I). Between February 10, 2003, and March 31, 2003, Florida vaccinated 4,434 individuals against smallpox. During this period a smallpox vaccine surveillance study was conducted in 18 counties in North Central Florida. The study was conducted via journal log, which participants completed daily by recording all symptoms, vaccination site stage development, and demographic information. The study included 350 vaccinees from Alachua, Baker, Bradford, Clay, Columbia, Dixie, Duval, Hamilton, Gilchrist, Lafayette, Levy, Flagler, Marion, Nassau, Putnam, Union, St. Johns, and Suwannee Counties. All symptoms experienced by study participants were normal and expected. Itching was experienced by 99.3% of the participants and site stage development was typical for the vaccinia virus. Naïve vaccinees had a longer mean vaccine site duration compared to non-naïve vaccinees.